The Effect of Intellectual Capital on MSME Performance Through Innovation as an Intervening Variable - Renya Rosari; Trinandari Prasetyo Nugrahanti; Laili Savitri Noor; Mohammad Muslimin; Akhmad Nur Zaroni (International Journal of Social Science and Business, 2024)
Micro, Small and Medium Enterprises (MSMEs) play an important role in the Indonesian economy. This study aims to explore the influence of intellectual capital on MSME performance through innovation. Using the purposive sampling method, questionnaires were distributed to 98 MSME owners in Indonesia. Data analysis was performed using Structural Equation Modeling (SEM) with the SMART PLS application. The results of SEM analysis show that intellectual capital has a positive effect on innovation (t-statistics = 120,105) and MSME performance (t-statistics = 18,863). In addition, innovation also has a positive effect on the performance of MSMEs (t-statistics = 12,010). This finding confirms that improving the performance of MSMEs requires strong intellectual capital and is supported by effective innovation. Thus, increasing innovation can be key in improving the performance of MSMEs. This research makes an important contribution in the understanding of the relationship between intellectual capital, innovation, and MSME performance. The implications of these findings can help MSME owners and related stakeholders to improve intellectual capital management strategies and innovations to improve the performance of MSMEs in Indonesia.